High speed electric motors based on high performance novel soft magnets - Silveyra, Josefina María (2014)
Novel Co-based soft magnetic materials are presented as a potential substitute for electrical steels in high speed motors for current industry applications. The low losses, high permeabilities, and good mechanical strength of these materials enable application in high rotational speed induction machines. Here, we present a finite element analysis of Parallel Path Magnetic Technology rotating motors constructed with both silicon steel and Co-based nanocomposite. The later achieved a 70% size reduction and an 83% reduction on NdFeB magnet volume with respect to a similar Si-steel design.